PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI DI SEKRETARIAT DAERAH KABUPATEN HALMAHERA TENGAH - Sofyan Senen; Sulfi Abdul Haji; Fahri, Johan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Abstract: This study aims to determine the influence of organizational culture and organizational commitment on organizational performance with job satisfaction as a mediating variable. This research is a quantitative study. The population in this study is calculated using the Slovin formula so that the sample in this study was 135 respondents. The data analysis technique used is path modeling with Smart Partial Least Square (PLS) version 4 as a statistical test tool. The results of this study indicate that: Organizational culture has a significant effect on organizational performance at the Regional Secretariat of Central Halmahera Regency, Organizational commitment does not have a significant effect on organizational performance at the Regional Secretariat of Central Halmahera Regency, Organizational culture has a significant effect on job satisfaction at the Regional Secretariat of Central Halmahera Regency, Organizational commitment has a significant effect on job satisfaction at the Regional Secretariat of Central Halmahera Regency, Job satisfaction has a significant effect on organizational performance at the Regional Secretariat of Central Halmahera Regency, Organizational culture has a significant effect on organizational performance through job satisfaction as a mediating variable at the Regional Secretariat of Central Halmahera Regency and Organizational commitment does not have a significant effect on organizational performance through job satisfaction as a mediating variable at the Regional Secretariat of Central Halmahera Regency.